61.5k views
4 votes
8(x – 3) – (6 – 2x) = 2(x + 2) – 5(5 – 2)

User Lizhen Hu
by
5.3k points

2 Answers

7 votes

8(x - 3) - (6 - 2x) = 2(x + 2) - 5(5 - 2)

8*x - 8*3 - 6 + 2x = 2*x + 2*2 - 5*3

8x - 24 - 6 + 2x = 2x + 4 - 15 ( Cancel equal terms on both sides of the equation)

8x - 24 - 6 = 4 - 15

8x - 30 = -11

8x = -11 + 30

8x = 19

x = 19/8

User Ozan Yurtseven
by
6.2k points
4 votes

Answer:

x=
(19)/(8)

Explanation:

8(x−3)−(6−2x)=2(x+2)−5(5−2)

Step 1: Simplify both sides of the equation.

8(x−3)−(6−2x)=2(x+2)−5(5−2)

8(x−3)+−1(6−2x)=2(x+2)−5(5−2)(Distribute the Negative Sign)

8(x−3)+(−1)(6)+−1(−2x)=2(x+2)−5(5−2)

8(x−3)+−6+2x=2(x+2)−5(5−2)

(8)(x)+(8)(−3)+−6+2x=(2)(x)+(2)(2)+−5(5−2)(Distribute)

8x+−24+−6+2x=2x+4+−15

(8x+2x)+(−24+−6)=(2x)+(4+−15)(Combine Like Terms)

10x+−30=2x+−11

10x−30=2x−11

Step 2: Subtract 2x from both sides.

10x−30−2x=2x−11−2x

8x−30=−11

Step 3: Add 30 to both sides.

8x−30+30=−11+30

8x=19

Step 4: Divide both sides by 8.

8x/8=19/8

Answer: x=
(19)/(8)

User Mohsin Qureshi
by
5.9k points